PENGARUH SUBSTITUSI TEPUNG SUKUN DENGAN TEPUNG AGAR TERHADAP SIFAT FISIK, KIMIA DAN SENSORIS BREADFRUIT BAR - , BESTARI AZAM MALIK; , Prof. Dr. Ir. Y. Marsono, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Increasing demand on wheat-flour based food results in increasing wheat flour import. Most of wheat flour traded is white flour which is low in dietary fiber. To reduce utilization ofwheat flour, local food flour can be used to subtitute wheat flour and to increase the dietary fiber content, agar powder can be added. The objective of this research is to determine the effect of breadfruit flour substitution with agar powder on the physical, chemical and sensory properties of breadfruit bar. Variation of 5, 10 and 15% of agar powder substitution was studied. Hardness value was determined with Universal Testing machine, chemical composition were determined using AOAC method, soluble and insoluble fibers were measured with enzymatic gravimetric method and sensoric properties were determined with attribute difference test method. The result showed that based on the texture attributes which match to the commercial product is breadfruit bar with 5% agar powder substitution. Substitution of agar powder have no significant effect on the sensory properties, but with the Universal Testing Machine it showed increase in hardness value of the product. Increasing substitution of agar powder substitution decreases the moisture, ash, protein and fat content but increases the carbohydrate content with the increase of soluble and insoluble dietary fiber of 0,17% and 2,09%, respectively.